Peningkatan Kreativitas Menggambar dengan Teknik Grafito di Taman Kanak-Kanak (TK) Negeri Pembina Santur Kota Sawahlunto - Artati, Hade; Ismed, Syahrul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study began with the results of observations that children were still not maximizing their creativity. This can be seen clearly from most children who always ask for help from teachers in doing the assignments given. Another thing can be seen from how children when doing activities that hone creativity such as drawing, imagining forming an object, they only focus on the shape exemplified by the teacher without creating a new shape or imagination. During drawing activities, children still seem confused and afraid to express their own ideas. In addition, when children are given the task of drawing, the classroom atmosphere is often crowded, children often walk around alone looking at their friends' drawings and are not serious with their own drawing books. The type used in this study is the type of classroom action research or PTK. The subjects in this study were children of State Kindergarten (TK) Pembina Santur City of Sawahlunto. The study was conducted in class A with 10 students. The location of this research was conducted at the State Kindergarten (TK) Pembina Santur, Sawahlunto City. This research was conducted in 2 cycles consisting of four main stages: planning, implementation of actions, observation, and reflection. Based on the results of the study, it was found that children's creativity increased through drawing activities with the graphitto technique, which can be seen from: the ability to color according to the steps exemplified increased from the initial condition of 20% to 70%. Children's ability to carry out activities neatly and cleanly increased from the initial condition of 0% to 70%. The ability to draw according to the child's imagination that will be conveyed increased from the initial condition of 10% to 80%. The ability to match the selection of light and dark colors used increased from the initial condition of 10% to 80%. The ability to complete a picture with the graphitto technique until finished increased from the initial condition of 10% to 70%.